Dexamethasone Administration in Mice Leads to Less Body Weight Gain over Time, Lower Serum Glucose, and Higher Insulin Levels Independently of NRF2 - Fotini Filippopoulou; George I. Habeos; Vagelis Rinotas; Antonia Sophocleous; Gerasimos P. Sykiotis; Eleni Douni; Dionysios V. Chartoumpekis (MDPI AG, 2021)
Glucocorticoids are used widely on a long-term basis in autoimmune and inflammatory diseases. Their adverse effects include the development of hyperglycemia and osteoporosis, whose molecular mechanisms have been only partially studied in preclinical models. Both these glucocorticoid-induced pathologies have been shown to be mediated at least in part by oxidative stress. The transcription factor nuclear erythroid factor 2-like 2 (NRF2) is a central regulator of antioxidant and cytoprotective responses. Thus, we hypothesized that NRF2 may play a role in glucocorticoid-induced metabolic disease and osteoporosis. To this end, WT and Nrf2 knockout (Nrf2KO) mice of both genders were treated with 2 mg/kg dexamethasone or vehicle 3 times per week for 13 weeks. Dexamethasone treatment led to less weight gain during the treatment period without affecting food consumption, as well as to lower glucose levels and high insulin levels compared to vehicle-treated mice. Dexamethasone also reduced cortical bone volume and density. All these effects of dexamethasone were similar between male and female mice, as well as between WT and Nrf2KO mice. Hepatic NRF2 signaling and gluconeogenic gene expression were not affected by dexamethasone. A 2-day dexamethasone treatment was also sufficient to increase insulin levels without affecting body weight and glucose levels. Hence, dexamethasone induces hyperinsulinemia, which potentially leads to decreased glucose levels, as well as osteoporosis, both independently of NRF2.